DEMOGRAPHIC STATUS OF MULTI DRUG RESISTANT TUBERCULOSIS PATIENTS IN FEW DISTRICTS OF SOUTHERN TAMILNADU - DR.R.NAVA JOTHI; ISAKKIRAJAN; DR.S. RAMESH KUMAR (International Journal of Pharma and Bio Sciences, 2016)
The objective of the study was to assess and enlist the demography of multi drug resistant -tuberculosis (MDR-TB) patients, which will give a clue on the risk factors in getting it. After getting the list of MDR TB diagnosed patients from Madurai District Tuberculosis Officer, Proforma, prepared for collecting details from selected MDR TB patients, was used to collect the details. One hundred multi drug resistant tuberculosis confirmed patients who were registered and taking anti-TB treatment from the district Revised National Tuberculosis Control Programme (RNTCP) were the study participants. Incidence of MDR TB was more in Males (69 %). 57% were in working age group (31 -50 years). 33 % were uneducated. Irregular treatment for Diabetes could be one of the risk factor. 56% were defaulters in CAT(Category )-1 & 32% were defaulters in CAT-2 antituberculous therapy . Defaulting, the main contributor to the Drug resistance is proved in our study. To reduce the number of MDR TB defaults, decentralization of the MDR TB treatment should be considered, either by creating community-based treatment programs or satellite inpatient centers. Doing Drug Sensitivity Testing (DST) for CAT-1 failures, before starting with CAT-2 treatment may lead to earlier diagnosis of MDR-TB.